Prognostic factors in hereditary breast cancer: A review - Ziske Maritska; Sarmoko (Indonesian Society for Biochemistry and Molecular Biology, 2024)
Hereditary breast cancer, primarily driven by BRCA1 and BRCA2 mutations, presents distinct challenges and prognostic factors compared to sporadic breast cancer. BRCA1-associated breast cancer is often triple-negative (TNBC), which has a more aggressive course and poorer prognosis. Despite this, BRCA mutation carriers exhibit higher sensitivity to platinum-based chemotherapy and PARP inhibitors, potentially improving outcomes. However, the risk of developing other malignancies, such as ovarian cancer and melanoma, remains elevated in BRCA mutation carriers. Studies show a significant variation in survival rates, with BRCA mutation carriers having lower overall survival compared to non-carriers. Loss of heterozygosity (LOH) in BRCA1/2 tumors is frequent but does not significantly alter overall survival rates. Identifying the presence of LOH can guide personalized treatment strategies, particularly the use of PARP inhibitors. The response to chemotherapy, especially platinum-based drugs, is influenced by genetic mutations such as TP53 and PTEN, which are common in TNBC. Surgical choices also impact prognosis; mastectomy may lower ipsilateral breast recurrence but does not affect overall survival. Pathologic complete response (pCR) following neoadjuvant chemotherapy is a critical prognostic marker, with higher rates observed in BRCA mutation carriers, particularly those with TNBC. These factors collectively influence the prognosis and guide treatment strategies for hereditary breast cancer.